PENEMUAN HUKUM OLEH HAKIM DALAM PRAKTEK HUKUM ACARA DI PERADILAN AGAMA - Abdul Manan (Jurnal Hukum dan Peradilan, 2013)
The court essentially banned refused to examine, decide a case filed with no legal argument or less clear, but obliged to examine and judge ". Provisions of this chapter gives the sense that as major organs Court judge and as executor of judicial power is obligatory for the Judge to find the law in a case despite legal provisions do not exist or are less clear. Law No. 48 of 2009 Article 5 (1) explains that "Judges shall multiply, follow and understand the values of law and justice that lives within the community. the judges in the religious court in making decisions on matters that should be examined and judged using the technique of taking decisions which include Analytical Techniques, Technical equatable, and techniques syllogism. Keywords: Rechtsvinding, Justice, Law Events, Religious Courts.